ALFRED NORTH WHITEHEAD’S APPROACH TO EDUCATION: IMPLICATIONS FOR RELIGIOUS EDUCATION - Hill, Brennan R. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1988)
This article examines Alfred North Whitehead’s educational theories with an eye on what implications these theories might have for contemporary religious education. Two central themes in Whitehead’s theory of education will be explored: 1) education as self-creation, and 2) education as a holistic experience. RÉSUMÉ Dans cet article, l’auteur examine les théories pédagogiques d’Alfred North Whitehead en s’interrogeant sur les conséquences que ces théories pourraient avoir sur l’éducation religieuse contemporaine. Il étudie deux thèmes centraux dans la théorie de l’éducation de Whitehead: 1) l’éducation en tant qu’autocréation, et 2) l’éducation en tant qu’expérience holistique.